2009
DOI: 10.1177/0273475309345202
|View full text |Cite
|
Sign up to set email alerts
|

Can Australian Universities Take Measures to Increase the Lecture Attendance of Marketing Students?

Abstract: Lectures are a central element of traditional university learning, but Australian lecturers increasingly face very low levels of lecture attendance. A significant amount of research exists that investigates the drivers of lecture attendance. However, those studies typically study single factors in an isolated manner, thus overestimating the importance of individual factors. This study contributes to the understanding of lecture attendance (and nonattendance) by including a range of factors that potentially aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…The majority of research into lecture attendance focuses on the reasons students do not attend lectures, assuming that reversing such conditions might increase attendance (Friedman et al 2001;Kottasz 2005;Massingham & Herrington 2006). For example, poor quality lecturing is one of the most common reasons cited for nonattendance at lectures (Dolnicar et al 2009). In response, research highlights the need to enhance the pedagogical skills of lecturers; Massingham and Herrington (2006), for example, suggest that today's students require a more student-centred approach.…”
Section: Practice Pointsmentioning
confidence: 99%
“…The majority of research into lecture attendance focuses on the reasons students do not attend lectures, assuming that reversing such conditions might increase attendance (Friedman et al 2001;Kottasz 2005;Massingham & Herrington 2006). For example, poor quality lecturing is one of the most common reasons cited for nonattendance at lectures (Dolnicar et al 2009). In response, research highlights the need to enhance the pedagogical skills of lecturers; Massingham and Herrington (2006), for example, suggest that today's students require a more student-centred approach.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Whilst all aspects are important, the influence of behavioural factors on student engagement is evidenced in part by strong correlations between attendance and attainment (Burd and Hodgson 2006;Colby 2005;Field 2012; Krause and Armitage 2014;van Schalkwyk et al 2010). In spite of this, attendance remains an issue within higher education and has been the subject of numerous investigations, including from the UK (Burd and Hodgson 2006;Field 2012), Europe (Landin and Pérez 2015), USA (Friedman et al 2014), South Africa (van Schalkwyk et al 2010) and Australia (Dolnicar et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although only 6% student had a part-time status in this research, there is a growing concern in Australian universities about the absenteeism from classes that adversely affects student performance (Rodgers, 2002). Research has shown that the level of class attendance varies between 7% and 70% in Australia (Dolnicar, Kaiser, Matus, & Vialle, 2009). In addition, according to the Manual of Policies and Procedure at QUT, attendance is not normally compulsory and cannot be a part of assessment items to force attendance (Queensland University of Technology [QUT], 2011).…”
mentioning
confidence: 77%